Sharing benefits from coastal resources with rual communities in South Africa : the influence of institutional arrangements - Mbatha, Nonhlanhla Philile (Department of Environmental and Geographical Science, 2015)
Through an analysis of three rural communities in these provinces, this research sought to understand how and why benefits arising from the use of coastal resources in the fisheries and mining sectors are shared and distributed in the manner that they are.